Effect of oxytocin infusion versus tranexamic acid on reducing blood loss during hysteroscopic myomectomy: a randomized controlled trial - Mohamed, Sabry E.; El Helaly, Amr M.; Salama, Mohamed H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Women undergoing hysteroscopic myomectomy are prone to significant blood loss and hematological disturbances. Oxytocin is a uterotonic drug, used mainly in obstetric practice. Tranexamic acid is a haemostatic drug that has been used to reduce blood loss after trauma and in many surgeries. The aim of our study was to compare the safety and efficacy of oxytocin versus tranexamic acid in reducing perioperative blood loss during hysteroscopic myomectomy. Methods: This study included 60 patients scheduled for hysteroscopic myomectomy allocated into 2 groups: group A: received 10 mg/kg of tranexamic acid slowly intravenous after induction of anesthesia, while group B: received infusion of 10 IU of oxytocin at a rate of 400 mIU/min throughout the procedure. Preoperative and postoperative hemoglobin and hematocrit levels, need for blood transfusion, duration of operation, complications and medications adverse effects were recorded. Results: The 2 groups were comparable in terms of the mean difference between preoperative and postoperative hemoglobin a hematocrit levels, operative time, operative complication and medications’ adverse effects. No patients needed blood component transfusion in either group. Conclusions: It can be concluded that tranexamic acid and oxytocin are equally effective in reducing blood loss and transfusion requirements during hysteroscopic myomectomy with comparable good safety profiles. Both of them can be used according to availability and surgeon preferences.